Modelo de monitoreo geológico- geotécnico mediante convergencias para definir el sostenimiento final de un túnel con fines civiles y mineros - túnel de conducción de la Central Hidroeléctrica Cheves - Ángeles Bazán, Richard Eduardo (2021)
The research analyzes the results obtained from applying the geotechnical monitoring model through convergences in the conduction tunnel of the Cheves hydroelectric plant - located in the district of Churín, province of Oyón, department of Lima. The conduction tunnel is 9693 meters long; during the underground excavation process using the New Austrian Tunnel Construction Method, which integrates the principles of the behavior of rock masses subjected to loads and the monitoring of the efficiency of underground construction. In the underground excavation, the geological contact between the Casma Group and the Chimú Formation is intercepted, which was affected by the post Intrusive Churín event, which increased the areas of weakness in the Casma Formation, such as geological faults filled with expansive minerals that are dipping to the ground. inside the tunnel shaft.The initial support of the conduction tunnel was defined after having been evaluated by means of geomechanical classification; Subsequently, in the sections where the intensity of fracturing that originates soft rocks that make up the rocky massif was evidenced, convergence stations were installed, in order to monitor the deformation in time and space of the installed support, thus applying the geotechnical monitoring model. Consequently, the objective was to analyze the result of applying the geotechnical monitoring model in the conduction tunnel, underground excavation, of the Cheves-Churín hydroelectric plant, which served to define and corroborate the stability of the conduction tunnel, related to the support applied in the underground excavation of said tunnel.